2017
DOI: 10.1007/s40273-017-0596-z
|View full text |Cite
|
Sign up to set email alerts
|

Using Real-World Data in Health Technology Assessment (HTA) Practice: A Comparative Study of Five HTA Agencies

Abstract: BackgroundReimbursement decisions are conventionally based on evidence from randomised controlled trials (RCTs), which often have high internal validity but low external validity. Real-world data (RWD) may provide complimentary evidence for relative effectiveness assessments (REAs) and cost-effectiveness assessments (CEAs). This study examines whether RWD is incorporated in health technology assessment (HTA) of melanoma drugs by European HTA agencies, as well as differences in RWD use between agencies and acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 25 publications
3
91
0
Order By: Relevance
“…However, a recent study found that policies for the use of RWD in relative effectiveness assessment vary across agencies, which presents challenges when using these data for HTA. 36 Therefore, in order to fully exploit the potential of RWD, agencies and pharmaceutical companies need to collaborate in order to provide guidance on data acquisition, management, and use across a range of settings. 37 …”
Section: Potential Uses Of Rwdmentioning
confidence: 99%
“…However, a recent study found that policies for the use of RWD in relative effectiveness assessment vary across agencies, which presents challenges when using these data for HTA. 36 Therefore, in order to fully exploit the potential of RWD, agencies and pharmaceutical companies need to collaborate in order to provide guidance on data acquisition, management, and use across a range of settings. 37 …”
Section: Potential Uses Of Rwdmentioning
confidence: 99%
“…In other examples, unpublished data were used to provide contextual information (other than effectiveness or harms/safety information); for example, to detail uptake of services, patient characteristics, epidemiology, natural history, or cost or data for cost-effectiveness analyses. [19][20][21][22][23] In some instances, the rationale for using unpublished data was not evident and/or appeared opportunistic (i.e., researchers had access to their own unpublished data and included it because it was available), and was not applied to healthcare decision making. Overall the examples we identified applied clinical practice data or specific registry data from a single health system (e.g., Mayo Clinic) or regional or nationally representative data (e.g., clinical registries, hospital database).…”
Section: Inform Strength Application or Implementation Of Evidencementioning
confidence: 99%
“…Another driver will be the progressive use of so-called real-world data—data obtained not from randomized trials but from more heterogeneous groups of patients already under treatment or observation. 37 In the future, strategic purchasers will make greater use of granular data on population and health services. The main challenge will probably remain the same as described earlier: solutions will have to combine data of very different natures from very different sources.…”
Section: How Digitalization Enhances the 3 Functions Of Health Financmentioning
confidence: 99%